Challenges and solutions to talent (de)selection and development in a youth soccer academy: the implementation of a multidisciplinary athlete profiling tool - Barraclough, Sam; Till, Kevin; Kerr, Adam; Emmonds, Stacey (Frontiers in Psychology, 2025)
Youth male soccer is more competitive than ever as clubs strive to recruit, develop, and produce future elite soccer players. Within youth soccer academies, it is important to recognise that, talent development (TD) and (de)selection are on-going and complex multidisciplinary processes with several challenges. Part 1 of this paper presents three real-world practical challenges including: (1) the ability to differentiate between performance and potential, (2) understanding and alignment to develop talented players, and (3) decision-making processes and (de)selection of players. The paper then presents a possible solution to these challenges demonstrated through the application of a multidisciplinary profiling tool created and utilised within a youth male soccer academy in the UK (Part 2). Finally, Part 3 of the paper identifies the applied challenges associated with implementing such a tool within a TD environment and provides possible solutions for effective implementation. The creation and implementation of the multidisciplinary athlete profiling tool can facilitate TD, and support (de)selection decisions. The solutions provided may serve as principles that can be flexibly implemented across a variety of sports and environments to augment TD and (de)selection processes.